Work on Oneself: Rethinking Authenticity - Jochen Schmidt (Religious Inquiries, 2018)
This article addresses the concept of authenticity, a characteristic of late modern Western culture. This characteristic is viewed by some as an ideal and by others as a root of the problems inherent within Western culture. After discussing various viewpoints, the author supports the idea that authenticity should not be totally accepted or rejected and sets forth a proposal based on the so-called “negative ethics” or “skeptical ethics”.